Improvement in maternal child bonding and lactation establishment with antenatal counseling - Meshram, Pallavi S.; Kania, Prema; Giri, Avinash B. (International Journal of Research in Medical Sciences, 2023)
Background: Breastfeeding (BF) is best food source for infants to improve child health, maternal health and mother-infant bonding. We aimed to assess the effect of antenatal education in increasing the frequency and duration of breast feeding and helpful in increasing the intimacy of mother and child and further improve the maternal and fetal outcomes. Methods: It is a prospective, randomized and interventional study held at tertiary care hospital for 18 months on 200 pregnant females. The counselled group (n=100) received one session of antenatal breastfeeding education, while the non-counselled group received routine antenatal obstetric care with no special intervention applied. Results: It was observed that the mean age and education of the mothers in the counselled as well as non-counselled group was statistically similar. The mean ANC visits, early initiation of BF, mean BSES and exclusive BF, were significantly higher in the counselled group as compared to non-counselled group. Complications are more in non-counselled group mothers. Conclusions: This study results demonstrate that a meaningful breastfeeding support and clinical health education can improve exclusive BF and BF self-efficacy with lowers the risk of complications.